Amplitude and Phase Tuning of Microwave Signals in Magnetically Biased Permalloy Structures - Martino Aldrigo; Alina Cismaru; Mircea Dragoman; Sergiu Iordanescu; Emanuela Proietti; Giovanni Maria Sardi; Giancarlo Bartolucci; Romolo Marcelli (IEEE Access, 2020)
In this paper, a permalloy layer has been employed in the fabrication of a coupled line electromagnetic bandgap (EMBG) device to tune both amplitude and phase. A magnetically biased microwave coplanar configuration manufactured with evaporated permalloy has been measured, and a circuit modelling has been studied to evaluate the measured effects in terms of variable attenuation and phase shift. Starting from a permalloy made by the mixture 80% nickel and 20% iron content, we fabricated an electromagnetic bandgap (EMBG) structure based on a periodic arrangement of single sections of a transmission line with variable impedance, also including a central region with coupled lines. The bandpass characteristics of the EMBG device can be tuned by changing permalloy's permeability through the application of a DC magnetic field H0 (parallel to the plane of the structure). In particular, using a magnetic field up to 3000 Oe, it was possible to change the phase by ca. 45° and the amplitude by ca. 7 dB in the X band.